Lingua Leap Board Game for Grammar Mastery: Permainan Papan Lingua Leap untuk Penguasaan Tata Bahasa - Kurniadiansyah, Meysha Dwi; Megawati, Fika (Indonesian Journal of Education Methods Development, 2025)
Background: Grammar mastery remains challenging for EFL learners, especially in secondary education where engagement is often low. Specific Background: Traditional instructional methods rarely integrate strategic decision-making and enjoyable learning experiences. Gap: Few studies provide non-digital board games specifically designed to reinforce the five basic English tenses through gamification. Aim: This study aims to present Lingua Leap, an instructional board game that supports grammar learning through structured challenges and game-based elements. Results: The game incorporates multiple difficulty levels, reward–penalty systems, and decision-based challenges that require learners to think critically while practicing Simple Present, Present Continuous, Simple Past, Past Continuous, and Simple Future tenses. Novelty: Lingua Leap offers a culturally aligned and curriculum-based non-digital game integrating strategy and linguistic practice. Implications: This product can serve as an engaging supplementary medium in EFL classrooms, supporting motivation, retention, collaboration, and meaningful grammar learning. Highlights• Board game for grammar learning• Multilevel challenge-based design• Strategy-oriented gamification Keywords: Board Game, Grammar Learning, Gamification, Tense Mastery, EFL Learners